2016
DOI: 10.1177/1687814016674384
|View full text |Cite
|
Sign up to set email alerts
|

Research on unmanned combat aerial vehicle robust maneuvering decision under incomplete target information

Abstract: This article investigates the problem of designing a novel maneuvering decision-making method for the unmanned combat aerial vehicle. The design objective is to promote the real-time ability of decision-making method and solve the problem of uncertainty caused by incomplete target information. On the basis of statistics theory, a robust maneuvering decision method with self-adaptive target intention prediction is proposed. The robustness design is embedded in the membership function of the situation parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The maneuver libraries of both sides are equal. The decisionmaking method of the enemy fighter is identical to the method in [12], which can be summarized as selecting the maneuver with the maximum situation function value in the next stage at each decision-making time-step.…”
Section: B Victory or Defeat Judgement Of Air Combat 1) Decision-makmentioning
confidence: 99%
See 2 more Smart Citations
“…The maneuver libraries of both sides are equal. The decisionmaking method of the enemy fighter is identical to the method in [12], which can be summarized as selecting the maneuver with the maximum situation function value in the next stage at each decision-making time-step.…”
Section: B Victory or Defeat Judgement Of Air Combat 1) Decision-makmentioning
confidence: 99%
“…However, ADP limited aircraft within the horizontal plane, and only three maneuvers were used. Wang et al [12] proposed a robust maneuvering decision method. They improved the membership function of situation evaluation during the decision process on the basis of the MIN-MAX decision method to make the situation function have a certain insensitivity to changes in the air combat situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7], it was shown that it is possible to guide a UCAV in close-range combat using the virtual pursuit point, effectively replacing a list of standard maneuvers (as in [2]) with a single guidance law, thus allowing real-time simulation for simplified UCAV flight dynamics. Unlike in [7], the work in [8] did not use a guidance law but employed the basic maneuver library of [2], albeit extending the number of elemental maneuvers from seven to eleven to account for increased maneuvering capabilities of UCAVs when compared to manned aircraft.…”
Section: A Existing Approachesmentioning
confidence: 99%
“…However, the game associated with DF engagements is not simple so that the corresponding game tree is large and thus it is computationally expensive to evaluate all possible states [10]. As pioneered in [2], and followed in [8] among others, it is often necessary to obtain quickly an approximate solution of the DF game rather than bear the prohibitive cost of finding the exact solution.…”
Section: A Existing Approachesmentioning
confidence: 99%